The Influence of Work Motivation, Job Satisfaction, and Organizational Commitment on Employee Performance at PT. Gasing Group in Makassar City - Marni; Nurdin Latif; Yusram Adi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to analyze the effects of motivation, job satisfaction, and organizational commitment on employee performance at PT. Gasing Group in Makassar City. Primary data were gathered through interviews, observations, and questionnaire responses from employees at the PT. Gasing Group in Makassar City and secondary data were gathered from a variety of sources, including documentation and writing (books, reports, scientific works, and research results) and information from parties involved in the study (job descriptions, work procedures, and other references). sample in this study amounted to 55 respondents according to the number of employees of PT. Gasing Group Makassar City. This type of quantitative descriptive research uses the approach of Simple Correlation Analysis and Multiple Linear Regression to measure the relationship between variables using the SPSS 22.0 program. The results showed that work motivation, job satisfaction, and organizational commitment had a positive and significant effect on the performance of PT. Gasing Group Makassar City. The most dominant variable, job satisfaction, has the greatest effect on employee performance compared to the other 3 variables.